A Review of the Potential Use of Pinene and Linalool as Terpene-Based Medicines for Brain Health: Discovering Novel Therapeutics in the Flavours and Fragrances of Cannabis - Weston-Green, Katrina; Clunas, Helen; Jimenez Naranjo, Carlos (Frontiers in Psychiatry, 2021)
‘Medicinal cannabis’ is defined as the use of cannabis-based products for the treatment of an illness. Investigations of cannabis compounds in psychiatric and neurological illnesses primarily focus on the major cannabinoids, cannabidiol (CBD) and Δ9-tetrahydrocannabinol (Δ9-THC), which can benefit multiple illnesses manifesting cognitive impairment, neurodegeneration and neuro-inflammation, as well as chronic pain, epilepsy and post-traumatic stress disorder, respectively. The cannabis plant contains >500 compounds, including terpenes responsible for the flavour and fragrance profiles of plants. Recently, research has begun providing evidence on the potential use of certain plant-derived terpenes in modern medicine, demonstrating anti-oxidant, anti-inflammatory and neuroprotective effects of these compounds. This review examined the effects of two key terpenes, pinene and linalool, on parameters relevant to neurological and psychiatric disorders, highlighting gaps in the literature and recommendations for future research into terpene therapeutics. Overall, evidence is mostly limited to preclinical studies and well-designed clinical trials are lacking. Nevertheless, existing data suggests that pinene and linalool are relevant candidates for further investigation as novel medicines for illnesses, including stroke, ischemia, inflammatory and neuropathic pain (including migraine), cognitive impairment (relevant to Alzheimer’s disease and aging), insomnia, anxiety and depression. Linalool and pinene influence multiple neurotransmitter, inflammatory and neurotrophic signals as well as behaviour, demonstrating psycho-activity (albeit non-intoxicating). Optimising the phytochemical profile of cannabis chemovars to yield therapeutic levels of beneficial terpenes and cannabinoids, such as linalool, pinene and CBD, could present a unique opportunity to discover novel medicines to treat psychiatric and neurological illnesses; however, further research is needed.